Peningkatan Motivasi Belajar Mata Pelajaran IPA Melalui Penerapan Startegi Everyone Is A Teacher Here Pada Siswa Kelas V SD Muhammadiyah 14 Surakarta Tahun 2015/2016 - PUTRI ISNIYONO, ERMI (2016)
This study aims to determine whether the strategy Everyone Here Is A Teacher can improve motivation and learning outcomes subject is science in class V students of SD Muhammadiyah 14 Surakartatahun 2015/2016. Subject of research that Vgrade teacher and V grade students of SD Muhammadiyah Surakarta 14 of 24 students. This research is a class act. Research was conducted during two cycles or four meetings. Each - each cycle consisting of the stages of action planning, action, observation and reflection. Collecting data through interviews, observation, and documentation. The results showed an increase in student motivation, namely: 1) the pre-stage cycle of 12.5%, 2) At the stage of the first cycle of 28.2%, 3) in the second cycle at 79.2%. As for improving student learning outcomes, namely: 1) the pre-cycle of 25.0%, 2) at this stage of the first cycle of 37.5%, 3) at this stage of cycle II of 79.2%. The conclusion of this study is strategic Everyone Here Is A Teacher can improve motivation and learning outcomes in grade V SD Muhyammadiyah 14 Surakarta in 2015/2016.